HISTORISITAS POTRET ISLAM DI AMERIKA - Wahyuni, Anjar Sri (ASKETIK, 2018)
The American state that it became the object of the first Islamic dawah in about 1875, from what was then known as Greater Syria (Great Syria [now includes Syria itself, Lebanon, Jordan and Palestine]) until the end of World War I. Followed by a second wave, in the 1920s to then be stopped because of World War II. Immigration laws in this period are rather limiting. Only black or Caucasian people can enter the United States. Arabs are considered not to fall into the two categories. While the third wave, between the mid-1940s and mid-1960s took place along with the occurrence of important changes outside the United States. Muslims who enter the US in this category are more educated. Most of them migrated because of political oppression. At the same time, especially in the 1960s various changes took place in US immigration policy. The job market is expanding and the country needs potential immigrants to fill the posts. Here ethnic or racial boundaries are loosened. Then the fourth wave, lasting about 1967 and still going on until now. They are generally very fluid and fluent in English. Their immigration is in place for various reasons such as for the improvement of professional ability and avoiding Government oppression. They also have the intention to settle or preach Islam in this Country. And the fifth wave started from 1967 until now. Those who came to America in this wave, in addition to economic reasons, political factors are also the main reasons that encourage them to migrate. There are some proofs that Islam came to America long before Columbus and the West.